A Study on the Effectiveness of Energy Absorbing Rubber in Pin-Fixed Cable Restrainer of a Bridge. Issue 2 (June 2014) - Tamai, Hiroki; Uno, Mariko; Yuki, Yoichi; Sonoda, Yoshimi; Kasugai, Toshihiro
The Japanese specifications for highway bridges require unseating prevention devices to be installed on bridges as necessary. Recently, a new type of cable restrainer was developed where the assembly allows the cable to rotate without restriction on the brackets' mounting angle. Cylindrical rubber pieces are inserted around pins to absorb impact forces. However, no standard design method has been established for the shock absorbers so far. This paper presents the impact-resisting characteristics of a pin-fixed cable device; design indications for shock absorbers were acquired based on the results of impact tests on bracket models of actual restrainers. The results showed that the pin-fixed restrainers had sufficient impact resistance for all tested sizes and that the maximum impact load showed consistent trends. Finite element analysis was also performed on the device assuming hyper-elastic bodies for rubber pieces. The numerical results sufficiently represented the impact response trend obtained from the experimental results.